Growth Performance of Kappaphycus alvarezii and Kappaphycus striatus cultivated in Ekas Bay, East Lombok Regency, West Nusa Tenggara Province - Cokrowati, Nunik; Nuryatin, Nuryatin; Jayusri, Jayusri; Jum'at, Muhammad; Muahidah, Nuri (Department of Aquaculture, 2024)
alvarezii is a superior product of Indonesian fisheries, producing carrageenan which is used as a food, cosmetic, and medicinal ingredient. K. striatus is a carrageenan-producing red alga that began to be cultivated in the Ekas waters of East Lombok in 2023. K. striatus is more resistant to epiphytes and sudden climate change. The purpose of this study was to analyze the growth of Kappaphycus alvarezii and Kappaphycus striatus. The research was conducted in Ekas Bay, Jerowaru District, East Lombok Regency. The research was conducted from November 8, 2023, to January 8, 2024. This research used an experimental method with T-test analysis. Treatments in this research are the cultivation of K. alvarezii and K. striatus. Cultivation was carried out at Ekas Bay. Analysis of seaweed carrageenan was carried out in the Laboratory of Fish Production and Reproduction, Aquaculture Study Program, Faculty of Agriculture, Mataram University. The result of this research is K. striatus has a higher absolute weight of 154 g compared to K. alvarezii seaweed which is 72 g. The specific growth rate K. striatus higher at 2,98 % / day compared to K. alvarezii is 1, 98 % / day. The yield of carrageenan of K. alvarezii is 1,95% and K. striatus 0,88%. Antioxidant of K. alvarezii is 5,46 % and K. striatus is 7,42%. Chlorophyll K. alvarezii is 5,77 mg/l and K. striatus is 3,51 mg/l. The conclusion of this study is the growth of K. striatus is faster than K. alvarezii.